2007
DOI: 10.1080/02692170701474710
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Economic Choice to Participate in Sport: Results from the 2002 General Household Survey

Abstract: This article explores the decision to participate in sports activities in the United Kingdom using a qualitative choice framework. The consistency of the results with neoclassical theories of leisure, and heterodox economic theory, which embraces a psychological view of decision making and structure of demand, is assessed. Finding more support for the latter perspective, the implications of this for sports policy are discussed.Sports, participation, choice behaviour, B41, C2, D11, D12,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
167
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(190 citation statements)
references
References 17 publications
17
167
2
4
Order By: Relevance
“…The lower sport participation among socially vulnerable youngsters is due to social, financial, emotional, and/or physical reasons (Downward, 2007;Wicker, Hallmann, & Breuer, 2012). Because of these many factors influencing sport participation by socially vulnerable youngsters, intersectoral action by youth work organisations and local sports clubs is needed to increase sport participation among these youngsters.…”
Section: Introductionmentioning
confidence: 99%
“…The lower sport participation among socially vulnerable youngsters is due to social, financial, emotional, and/or physical reasons (Downward, 2007;Wicker, Hallmann, & Breuer, 2012). Because of these many factors influencing sport participation by socially vulnerable youngsters, intersectoral action by youth work organisations and local sports clubs is needed to increase sport participation among these youngsters.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, health status was an important determinant of physical/ psychological constraints. However, the negative effect of health status on sports frequency, which was also found by Downward (2007), remained significant after adding the physical/psychological constraints and other constraint factors to the model. Apparently, sports frequency was determined not by the constraints with respect to sports participation but rather by the direct measurement of health status.…”
Section: Interpretation Of the Main Findings Of Effects On Sports Frementioning
confidence: 94%
“…lack of appropriate accommodation) (Godbey, Crawford, & Shen, 2010). Those subjective constraints to sports participation have been found to play a significant negative role on sports participation and sports frequency (Alexandris & Carroll, 1997a;Casey et al, 2016;Downward, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This author concluded that men participate more in sports than women, and sports participation decreases with increasing age. Regarding the effect of gender on physical activity and sports participation, recent studies also show a greater predominance of male over female participation (Hovemann & Wicker, 2009) and increased interest from men when they participate in any physical activity or sport (Berger, O´Reilly, Parent, Séguin, & Hernández, 2008;Farrell & Shields, 2002;Humphreys & Ruseski, 2006, 2007Lera-López & Rapún-Gárate, 2005;Seabra, Mendonca, Thomis, Malina, & Maia, 2007;Taks & Scheerder, 2006). However, longitudinal studies indicate an increase in female participation (Baker, Fraser-Thomas, Dionigi, & Horton, 2010), which in recent years has surpassed male participation in some activities in Canada (Humphreys & Ruseski, 2010) and in some Scandinavian countries (Denmark, Finland, and Sweden) (Fridberg, 2010).…”
Section: Determinants Of Sports Participation: Gender Age and Natiomentioning
confidence: 99%
“…However, according to Ruseski, Humphreys, Hallmann and Breuer (2011), hours in the workplace does not affect participation, confirming that physical activity is leisure time activity, so that the time allocated to physical activity derives from non-work hours. Time is also included in the neoclassical approach in relation to sport as a major constraint in sport participation (Downward, 2007). In the family environment, Becker's theories suggest that distribution of activities among household members affects individual allocation of time (Downward, 2004).…”
Section: Introductionmentioning
confidence: 99%